Food systems and diets: Facing the challenges of the 21st century - Global Panel on Agriculture and Food Systems for Nutrition; Haddad, Lawrence James; Hawkes, Corinna; Waage, Jeff; Webb, Patrick; Godfray, Charles; Toulmin, Camilla; Aleksandrowicz, Lucasz; Baker, Phillip; Bhatia, Komal; Carrus, Giuseppe; Beed, Fenton D.; et al. (Global Panel on Agriculture and Food Systems for Nutrition, 2016)
This report includes important recommendations and advice for leaders at the most senior levels in countries and international organizations. It is also of direct relevance to all policy makers, decision makers, professionals, business people, experts and researchers with interests in food systems and diets. Many of these individuals will be directly concerned with the production, processing, trade, regulation, supply and safety of food. However, others may work in wider areas of policy and business, for example relating to: public health and well-being, mental health development, education, economic development, urbanization, globalization and demography.